A library research: teaching English to English language learners with learning disabilities - Siti Dwi Karmila; Jamie Harrison (Journal of English Language Teaching Innovations and Materials (Jeltim), 2019)
Lack of knowledge about learning disability makes the English teachers in developing non-English speaking countries hardly distinguish the presence of students with learning disability among their students in their general setting classroom. Then, when they are able to identify their students having learning disabilities, other problems comes up since the schools do not have enough resources and special education services. It is so problematic since they cannot send these students to special education school as learning disability (LD) is still considered mild to attend the special education school. Related to the problem mentioned, this paper provides some teaching strategies from some experts that can be used to teach both students with and without learning disability in general setting classroom. These teaching strategies will be collected through reviewing all empirical research related to the topic. The result of this paper is a set of collected strategies to teach English language learners (ELLs) with and/or without learning disability (LD).